2017
DOI: 10.1016/j.celrep.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Antitumor Immunity by Human and Mouse CAR T Cells Secreting IL-18

Abstract: SUMMARY The effects of transgenically encoded human and mouse IL-18 on T cell proliferation and its application in boosting chimeric antigen receptor (CAR) T cells are presented. Robust enhancement of proliferation of IL-18-secreting human T cells occurred in a xenograft model, and this was dependent on TCR and IL-18R signaling. IL-18 augmented IFN-γ secretion and proliferation of T cells activated by the endogenous TCR. TCR-deficient, human IL-18-expressing CD19 CAR T cells exhibited enhanced proliferation an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
260
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(264 citation statements)
references
References 30 publications
(34 reference statements)
3
260
0
1
Order By: Relevance
“…18 In this study, we investigated the IL-18R-independent pathway and its contribution to biological functions of IL-18 to CAR-T cells. We have demonstrated that IL-18 functions to enhance the antitumor activities of CAR-T cells through both IL-18R-dependent and independent pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In this study, we investigated the IL-18R-independent pathway and its contribution to biological functions of IL-18 to CAR-T cells. We have demonstrated that IL-18 functions to enhance the antitumor activities of CAR-T cells through both IL-18R-dependent and independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been identified as a pro-inflammatory and immunoregulatory cytokine. 18 Avanzi et al 19 proved that CAR-T cells secreting IL-18 could improve activity in syngeneic hematologic and solid tumor models without prior preconditioning, and enhance the antitumor response of endogenous T cells. 16,17 It has been recently reported that IL-18-secreting CAR-T cells have superior antitumor activity, achieved via the helper effect of CD4 + T cells on the promotion of CD8 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…119 ), IL-18 (ref. 120 ) and IL-21 (ref. 121 ) can help to promote the cells' proliferation and reshape the tumour microenvironment.…”
Section: Homing and Traffickingmentioning
confidence: 99%
“…[26][27][28][29] Strategies to modulate the local TME have led to the generation of 'armored' CAR T cells that provide localised expression of pro-inflammatory cytokines or costimulatory ligands to improve CAR T-cell function within tumors. 33,34 Other systems involving cytokine-mediated enhancement of CAR T cells include the genetic modification of these cells to express a form of membrane-bound chimeric IL-15, which gave rise to a population of CAR T cells that possessed a T memory stem cell phenotype and a better memory potential even in the absence of antigen stimulation. In these studies, CAR T cellsecreted IL-12 augmented their cytotoxic function and alleviated regulatory T cell (Treg)-mediated suppression.…”
Section: Localised Expression Of Immune-stimulatory Molecules By Carmentioning
confidence: 99%